Towards a methodology for including God’s voice in researching Church of England schools - Humphreys, Huw (International journal of Christianity & education, 2026)
Qualitative research investigates spiritual realities by inquiry into meanings, which are recorded by the researcher as observed actions or perceptions of individuals or groups. Such investigations can miss what for Christians is the reality of God?s agency, an ontology not accepted in most educational research. Using a ?tradition of rational discourse? based not simply on the Enlightenment paradigm but on the reality of God as understood in Jesus Christ enlarges the scope when researching God?s agency. I use chronotopic analysis to describe the ?truth regimes? underlying existing education research methodologies and explore how a Christian rational discourse fares within that analysis. Finding existing chronotopic analysis inadequate to recognise and respond to God?s agency, I develop and argue for a new chronotope rooted in a personalist interpretation of knowledge that allows for revelation, love and covenant in how we know. I apply this to researching in Church of England schools, with some indications of how it could become a practical tool for a more holistic research approach in Christian education.